Commercial Banks and Socio Economic Wellbeing of the People: A case study of Equity Bank Kabale Branch. - Timothy, Begambagyedo (Kabale University, 2020)
The study investigated the services and products offered by Commercial Banks in improving socio- economic wellbeing of the people. The specific objectives were; to assess terms and conditions of asset finance and development loans in improving the socio economic wellbeing of Equity Bank clients, to determine how access to asset finance, and development loans have contributed to the level of socio economic wellbeing by Equity Bank clients, and to establish the challenges faced by Equity Bank in providing asset finance and development loans for the socio economic wellbeing of its clients. The study revealed that application supported by documents like invoices and BOQs, Provision of financial information, employer must have an MOU with Equity Bank, having an employment opportunity and an active Bank account, a copy of valid identification document and ability to repay the loan, the study further established that credit risk is the leading challenge faced by Banks, inadequate appraisal, customers’ unwillingness to repay, political unrest, high interest from the regulatory authority and un stable economic trends in the country. It also revealed that pledging of collateral accounting, use of credit rating, use of collection agencies, entrepreneurial training, use of credit Reference Bureau, and adequate loan monitoring are some of the measures put in place to control loan default, the study recommends that the Bank should introduce entrepreneurial training of its clients before and after disbursement of the loan facility as this will enhance the performance of the loans given out. The study further recommends that the Commercial Banks should introduce and those that have maintain and upgrade the information technology to capture and control the history and progress on the loans that have been given out so as to reduce on the default rates of these commercial Banks The study also recommends that Banks should use Credit Reference Bureau as it provides information about the credit history of clients seeking facilities from the Bank.